The Antibiofilm Role of Biotics Family in Vaginal Fungal Infections - Boahen, Angela; Than, Leslie Thian Lung; Loke, Yi-Linn; Chew, Shu Yih (Frontiers in Microbiology, 2022)
‘Unity in strength’ is a notion that can be exploited to characterize biofilms as they bestow microbes with protection to live freely, escalate their virulence, confer high resistance to therapeutic agents, and provide active grounds for the production of biofilms after dispersal. Naturally, fungal biofilms are inherently resistant to many conventional antifungals, possibly owing to virulence factors as their ammunitions that persistently express amid planktonic transition to matured biofilm state. These ammunitions include the ability to form polymicrobial biofilms, emergence of persister cells post-antifungal treatment and acquisition of resistance genes. One of the major disorders affecting vaginal health is vulvovaginal candidiasis (VVC) and its reoccurrence which is termed recurrent VVC (RVVC). It is caused by Candida species which include Candida albicans and Candida glabrata. The aforementioned Candida species, notably C. albicans is a biofilm producing pathogen and habitually forms part of the vaginal microbiota of healthy women. Latest research have implicated the role of fungal biofilms in VVC, particularly in the setting of treatment failure and RVVC. Consequently, a plethora of studies have advocated the utilization of probiotics in addressing these infections. Specifically, the excreted or released compounds of probiotics which are also known as postbiotics are being actively researched with vast potential to be used as therapeutic options for the treatment and prevention of VVC and RVVC. These potential sources of postbiotics are harnessed due to their proven antifungal and antibiofilm prowess. Hence, this review discusses the role of Candida biofilm formation in VVC and RVVC. In addition, we discuss the application of pro-, pre-, post-, and synbiotics either individually or in combined regimen to counteract the abovementioned problems. A clear understanding of the role of biofilms in VVC and RVVC will provide proper footing for further research in devising novel remedies for prevention and treatment of vaginal fungal infections.